Deficiency of Suppressor T Cells in the Hyperimmunoglobulin E Syndrome - Geha, Raif S. (1981)
The status of suppressor T cells (Ts) was assessed in seven children with the hyper IgE syndrome (recurrent staphylococcal infections, eczematous skin rash, and elevated serum IgE) to determine whether a deficiency in Ts is associated with increased IgE synthesis. When circulating T cells and their subsets were enumerated with the aid of monoclonal antibodies that identify T cells (T3), helper/inducer T cells (T4), and suppressor/cytotoxic T cells (T8), there was a selective deficiency of T3+ cells (51.7±11.2% vs. 66±5% for normal controls) and of T8+ cells (7.5±4.4% vs. 22±4% for normal controls) but not of T4+ cells (36.5±7.5% vs. 37±3% for normal controls). Suppressor T cell function was assessed by examining the ability of mononuclear cells incubated for 48 h with concanavalin A to suppress the proliferation of fresh autologous mononuclear cells in response to the mitogens phytohemagglutinin and pokeweed mitogen. All seven patients were severely deficient in concanavalin A-inducible suppressor cells. In vitro de novo synthesis of IgE in 6-d cultures of peripheral blood lymphocytes was measured in four patients by a solid-phase radioimmunoassay. Mononuclear cells from all four patients synthesized spontaneously increased quantities of IgE in vitro (4,950±3,760 pg/10(6) cells vs. 250±215 pg/10(6) cells for eight normal controls). IgE synthesis was suppressed by the addition of parental T cells to the culture. Elimination of the T8+ subset, but not of the T4+ subset, by complement-dependent lysis resulted in the loss of the capacity of parental T cells to suppress IgE synthesis. These results suggest that a deficiency of Ts underlies the elevated IgE levels observed in the hyper IgE syndrome.